Effectiveness of cooperative learning in at the implementation of floral material for celli graph and decoration (Journal Of Educational and Psychological Researches, 2014)
The purpose of this resesrh know (the effectiveness of cooperative lerarning implementation of floral material for calligraphy and ornamentation) To achieve the aim of the research scholar put the two zeros hypotheses: in light of the findings of the present research the researcher concluded a number of conclusions, including: -1 - Sum strategy helps the learner to be positive in all the information and regulations, monitoring and evaluation during the learning process.2 - This strategy helps the learner to use information and knowledge and their use in various educational positions, and to achieve better education to increase its ability to develop thinking skills and positive trends towards the article.In light of this, the researcher put a number of recommendations concerning the results of research, including: - the need to adopt a strategic Tags in teaching, which enables students to employ their skills in guiding thought processes, and take personal responsibility in learning, based on the principle of self-learning.To complement the aspects of research suggest that the researcher the following:a similar study of the current study to know the impact of strategic Tags in variables other than a collection (such as motivation, direction and orientation towards the material, and expressive performance, and reasoning, etc.).